The Role of Recovery Phases in Mitigating the Negative Impacts of Marine Heatwaves on the Sea Star Asterias rubens - Wolf, Fabian; Seebass, Katja; Pansch, Christian (Frontiers in Marine Science, 2022)
During recent years, experimental ecology started to focus on regional to local environmental fluctuations in the context of global climate change. Among these, marine heatwaves can pose significant threats to marine organisms. Yet, experimental studies that include fluctuating thermal stress are rare, and if available often fail to base experimental treatments on available long-term environmental data. We evaluated 22-year high-resolution sea surface temperature data on the occurrence of heatwaves and cold-spells in a temperate coastal marine environment. The absence of a general warming trend in the data may in parts be responsible for a lack of changes in heatwave occurrences (frequency) and their traits (intensity, duration, and rate of change) over time. Yet, the retrieved traits for present-day heatwaves ensured most-natural treatment scenarios, enabling an experimental examination of the impacts of marine heatwaves and phases of recovery on an important temperate predator, the common sea star Asterias rubens. In a 68-days long experiment, we compared a 37- and a 28-days long heatwave with a treatment that consisted of three consecutive 12-days long heatwaves with 4 days of recovery in between. The heatwaves had an intensity of 4.6°C above climatological records, resulting in a maximum temperature of 23.25°C. We demonstrate that heatwaves decrease feeding and activity of A. rubens, with longer heatwaves having a more severe and lasting impact on overall feeding pressure (up to 99.7% decrease in feeding rate) and growth (up to 87% reduction in growth rate). Furthermore, heatwaves of similar overall mean temperature, but interrupted, had a minor impact compared to continuous heatwaves, and the impact diminished with repeated heatwave events. We experimentally demonstrated that mild heatwaves of today’s strength decrease the performance of A. rubens. However, this echinoderm may use naturally occurring short interruptions of thermal stress as recovery to persist in a changing and variable ocean. Thus, our results emphasize the significance of thermal fluctuations and especially, the succession and timing of heat-stress events.